Analysis and Structural Improvement of the KMP Portlink III Bow under Collision Loads Using the Finite Element Method - Yeremia Parasian Christover Manurung; Wiwin Sulistyawati (Fakultas Teknik UPN Veteran Jakarta, 2026)
Ship collision accidents can cause severe damage to the bow structure, as it is the first part of the vessel to receive impact loads. This study aims to analyze the structural response of the bow of KMP Portlink III under collision loads and to evaluate the effectiveness of adding carlings in improving structural strength. The bow structure was modeled using Autodesk Fusion, while the numerical analysis was carried out using Autodesk Inventor based on the Finite Element Method (FEM). The analysis was conducted on four design configurations, namely the original design, horizontal carling, vertical carling, and combined carling, with loading variations of 100%, 104%, 106%, 108%, and 110% of the initial collision load of 1,191,900 N. The evaluated parameters included Von Mises stress and safety factor. The results indicate that increasing the collision load leads to higher Von Mises stress and lower safety factor values. The addition of carlings effectively reduced the maximum stress and increased the safety factor, with the combined carling design providing the best structural performance in improving the bow's resistance to collision loads. Keywords: collision load, Finite Element Method, Von Mises stress, safety factor, carling.